Electrochemical deposition of ZnO nanorods on transparent reduced graphene oxide electrodes for hybrid solar cells - Yin, Zongyou (2012)
Monocrystalline ZnO nanorods (NRs) with high donor concentration are electrochemically deposited on highly conductive reduced graphene oxide (rGO) films on quartz. The film thickness, optical transmittance, sheet resistance, and roughness of rGO films are systematically studied. The obtained ZnO NRs on rGO films are characterized by X-ray diffraction, transmission electron microscopy, photoluminescence, and Raman spectra. As a proof-of-concept application, the obtained ZnO NRs on rGO are used to fabricate inorganic–organic hybrid solar cells with layered structure of quartz/rGO/ZnO NR/poly(3-hexylthiophene)/poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (P3HT/PEDOT:PSS)/Au. The observed power conversion efficiency (PCE, η), ≈ 0.31%, is higher than that reported in previous solar cells by using graphene films as electrodes. These results clearly demonstrate that rGO films with a higher conductivity have a smaller work function and show a better performance in the fabricated solar cells.